1985
DOI: 10.1210/jcem-60-5-967
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cortisol Resistance Accompanied by a Reduction in Glucocorticoid Receptors in Two Members of the Same Family*

Abstract: This report describes studies of a man suspected of having primary cortisol resistance. This conclusion is based on his high plasma cortisol levels and high 24-h urinary 17-hydroxycorticosteroid and cortisol excretion, plus the fact that he had no manifestations of Cushing's syndrome. Among family members tested, his mother also had hypercortisolemia. Both mother and son had high levels of unbound plasma cortisol, but their plasma ACTH concentrations were within the normal range. Both were partially resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…This is supported by studies describing the absence of Cushingoid features and metabolic abnormalities in hypercortisolemic patients (21) and, conversely, the manifestation of the Cushing's syndrome phenotype in hypocortisolemic patients (22).…”
mentioning
confidence: 69%
“…This is supported by studies describing the absence of Cushingoid features and metabolic abnormalities in hypercortisolemic patients (21) and, conversely, the manifestation of the Cushing's syndrome phenotype in hypocortisolemic patients (22).…”
mentioning
confidence: 69%
“…Primary glucocorticoid resistance due to inherited abnormalities of the glucocorticoid receptor (GR) have been described (Iida et al 1985) but very few cases have been reported worldwide and there are no reports in the literature of IBD patients with primary glucocorticoid resistance or grossly elevated cortisol levels characteristic of this condition. However, most glucocorticoid resistance research on T-lymphocytes and other target inflammatory cells have demonstrated several GR abnormalities as potential mechanisms influencing response to glucocorticoid treatment in several inflammatory conditions.…”
Section: Glucocorticoid Receptor Abnormalities and Glucocorticoid Resmentioning
confidence: 99%
“…6, and references therein] or decreased receptor content [7]. A direct correlation between the number of GRs and cellular responsiveness to the hormone has been documented in a variety of cell lines [8][9][10][11] as well as in human subjects [12][13][14][15][16][17][18].…”
Section: Glucocorticoidmentioning
confidence: 99%